Performing Curative Medical Experiments on Incurable Patients: Between Islamic Jurisprudence and the Laws of the Middle East - Hammad, Hamza Abed AlKarim (Mazahib, 2024)
This study aims to elucidate the Islamic jurisprudential and legal ruling on conducting curative medical experiments on incurable patients. The study found it appropriate to divide those experiments into two parts. Firstly, medical experiments on incurable patients to secure a cure for the illness from which they suffer. Secondly, Medical experiments on incurable individuals produce a cure for an illness from which they do not suffer. The present study adopted the descriptive method grounded in describing the issue and then comparing and analyzing the jurisprudential opinions leading to the chosen opinion. The Study concluded that Emirati and Jordanian Laws and Islamic jurisprudence find it permissible to conduct medical treatment experiments underpinned by a set of parameters and restrictions.